Perceptions of selected Master of Library and Information Science graduates on the possible implementation of the Library and Information Science Ph. D. course in Ateneo de Manila University - Lumbre, Nathaniel B. (2014)
The study focused on the market feasibility of the LIS Ph.D. course of the Ateneo de Manila University. The study intended to determine and analyze the perceptions of Master of Library and Information Science graduates on the possible Implementation of LIS doctorate course in AdMU. A total of 17 respondents, who are all MLIS degree holders from the University of the Philippines School of Library and Information Studies, answered the online survey questionnaire administered by the researcher.